God as a Servant of Magic? The Challenge of the Impersonalisation of God in Neo-Pentecostal Prophetic Responses to Human Agency and Transcendence in Africa - Banda, Collium (Religions, 2022)
This article is a Christian theological evaluation of African neo-Pentecostal prophets’ (ANPPs) projection of God as a servant of prophetic rituals in their solutions to poor human agency (power to act) and transcendence (power to overcome) in Africa. Instead of propagating a personal relational God who transforms the poor and empowers their agency and transcendence by personally engaging with them, ANPPs propagate a God who works by ritual manipulation. The main question answered in the article is: what is the notion of God that informs and guides the ANPPs’ engagement with human agency and transcendence in Africa? The question is answered by first presenting a framework of God’s personality. The ANPPs’ impersonalized view of God is described. The basis of the impersonalisation of God in ATR is presented. The vulnerability of human agency and transcendence as a result of the impersonalisation of God is described. The article closes by proposing how a personal Trinitarian view of God rejects the ANPP impersonalisation of God and describes how the Trinitarian view can assist in addressing the problem of human agency and transcendence among poor Africans. The contribution of the article lies in challenging ANPPs to desist from addressing poor human agency and transcendence in Africa by propagating a version of God who is a servant of magical rituals instead of a relational God who is personally involved with the poor to empower them to overcome the hindrances to their human flourishing.